Growth and production of Melia dubia under silvi-pasture systems and sole plantations: positive implications of intercropping hybrid napier - Prajapati, D R; Thakur, Narender Singh; Gunaga, R P; Bhuva, D C (Indian Journal of Agroforestry, 2023)
Growth and yield performance of Melia dubia was evaluated under silvi-pasture systems [M. dubia- Hybrid napier (HN)] and sole plantations, to ascertain effect of intercropping HN for two years. The study was comprised of ten treatments: land uses- LU1 to LU5 [M. dubia (2 × 2 or 3 × 3 or 3 × 2 or 4 × 4 or 4×2 m) + HN] and LU6 to LU10 sole M. dubia with same spacing) with four replications following Randomized Block Design. Results revealed that, at planting (January, 2018) and final HN forage harvest (December, 2019), significantly (p<0.05) maximum tree height was under M. dubia (3 x 3 m)-HN system. Initially, maximum DBH was under sole plantation spaced at 4x4 m, however, at final HN forage harvest, DBH was highest under M. dubia (4x4 m)-HN system. Maximum height (4.00 m) and DBH (8.55 cm) increment, over two years, was gained by trees in M. dubia (4 x 2 m)-HN system. At HN planting, sole M. dubia (4 x 4 m) had maximum fresh biomass (18.28 kg tree-1) and over bark volume (0.015 m3 tree-1), however, at final HN harvest, maximum fresh biomass (78.94 kg tree-1), over bark volume (0.076 m3 tree-1) and increment (62.32 kg tree-1 and 0.063 m3 tree-1 in biomass and volume, respectively) was of trees in M. dubia (4 x 4 m)-HN silvi-pasture system. This indicates positive implication of HN intercropping, which enhanced growth and yield of M. dubia.